S60. A PRELIMINARY COMPARISON OF COGNITIVE CHANGE: MINDFULNESS MEDITATION V. COGNITIVE REMEDIATION. (18th May 2020) - Carruthers, Sean; Louise, Stephanie; Lee, Stuart; Bryce, Shayden; Tan, Eric; Reser, Maree; Thomas, Neil; Rossell, Susan
Abstract: Background: Schizophrenia spectrum disorder (SSD) typically presents with a diverse range of cognitive impairments, with the effective treatment of which is advocated as an important future focus for the field. Currently, cognitive remediation therapy (CRT) is the most widely administered form of cognition enhancing treatment, however individual responses to CRT are highly variable in SSD, warranting examination of whether alternative approaches can also enhance cognition. Mindfulness-based interventions (MBI) have shown potential in alleviating the negative impact of clinical SSD symptoms and show promising pro-cognitive treatment effects. The aim of the current study was to retrospectively compare cognitive improvements following two different CRT programs (multi-domain drill and strategy; visually intensive drill and practice) an MBI targeting persistent auditory verbal hallucinations, and a video game-based active control. Methods: Data was retrospectively pooled for participants who completed measures of perceptual processing speed, sustained and switching attention, and inhibitory control. Twelve SSD participants completed four weekly one-hour individual sessions of the Individual Mindfulness Program for Voices, 22 completed a minimum of ten one-hour group-/computed-based sessions of the multi-domain drill and strategy intervention COGPACK, 22 completed a minimum of 24 one-hour group-/computer-based sessions of BrainHQ's (Posit Science) VISUAL Intensive drill and practice intervention, and 17 participants completed a minimum of 10 one-hour group-/computed-based sessions of games putatively similar to exercises common to CRT (active control). Baseline/Post-treatment change effects were calculated for each intervention across specified cognitive variables and converted to standardised Z-scores based on the performance of the active control group. Results: Unique and overlapping pro-cognitive effects were identified for each of the three intervention types compared to the active control. MBI produced moderate standardized pro-cognitive effects above the active control in perceptual processing speed (z-score□: 0.62) and switching attention (z-score: 0.45). This somewhat overlapped with the change effects calculated for the visually intensive drill and practice (z-score□: 0.57) CRT program. Both the visually intensive drill and practice (z-score: 0.47) and the multi-domain drill and strategy (z-score: 0.52) CRT programs resulted in moderate-to-large improvements v. control in sustained attention, whilst the MBI had no such effect (z-score: 0.10). The video-gamed based active control produced moderate improvements in inhibitory control in comparison to all three interventions (z-score□: -0.37). Discussion: Overall, these preliminary findings suggest that a brief MBI can produce similar performance enhancing effects to that of the lengthier CRT programs in a discrete subset of cognitive tests. More extensive examinations of the cognitive benefits and their translation to real world functional improvements in SSD are needed.